Effects of covering highland banana stumps with soil on banana weevil Cosmopolites sordidus (Coleoptera: Curculionidae) oviposition - Masanza, M.; Gold, C.; Huis, A. van; Ragama, P.E. (Springer, 2005)
The effect of covering post-harvest banana stumps with soil on banana weevil Cosmopolites sordidus (Germar) oviposition levels was investigated at three locations, Sendusu, Kawanda Agricultural Research Institute (KARI) and Ntungamo district of southwestern Uganda. In the first experiment oviposition levels were assessed in a banana system comprising growing plants and residues. Oviposition increased on sword suckers, reaching a peak 1–7 days after harvest and decreased thereafter. In the second experiment conducted on farmers' fields, corms received 70% of the eggs and pseudostems 30%. The area 5–10 cm below the collar received 27% of the eggs, the area 0–5 cm above the collar 30% and the area 5–10 cm above the collar 0.3%. The remaining eggs (43%) were laid 0–5 cm below the collar. The effect of stump height and covering the stumps was evaluated in both the wet and the dry seasons at Kawanda and Ntungamo. Cutting stumps to the ground level alone had no effect on oviposition. Covering post-harvest banana stumps reduced C. sordidus oviposition in the wet but not in the dry season.